The surprising ingredients of Swedish success: Free markets and social cohesion - Nima Sanandaji (Institute of Economic Affairs (IEA), 2012)
New IEA paper demonstrates that Swedish success is a result of the free market and not the welfare stateExecutive Summary:Sweden did not become wealthy through social democracy, big government and a large welfare state. It developed economically by adopting free-market policies in the late 19th century and early 20th century. It also benefited from positive cultural norms, including a strong work ethic and high levels of trust.As late as 1950, Swedish tax revenues were still only around 21 per cent of GDP. The policy shift towards a big state and higher taxes occurred mainly during the next thirty years, as taxes increased by almost one per cent of GDP annuallyThe rapid growth of the state in the late 1960s and 1970s led to a large decline in Sweden's relative economic performance. In 1975, Sweden was the 4th richest industrialised country in terms of GDP per head. By 1993, it had fallen to 14th.Big government had a devastating impact on entrepreneurship. After 1970, the establishment of new firms dropped significantly. Among the 100 firms with the highest revenues in Sweden in 2004, only two were entrepreneurial Swedish firms founded after 1970, compared with 21 founded before 1913.High levels of equality and favourable social outcomes were evident before the creation of an extensive welfare state. Moreover, generous welfare policies have created numerous social problems, including high levels of dependency among certain groups.Descendants of Swedes who migrated to the USA in the 19th century are characterised by favourable social outcomes, such as a low poverty rate and high employment, despite the less extensive welfare state in the USA. The average income of Americans with Swedish ancestry is over 50 per cent higher than Swedes in their native country.Third World immigrants have been particularly badly affected by a combination of high welfare benefits and restrictive labour market regulations. In 2004, when the Swedish economy was performing strongly, the employment rate among immigrants from non- Western nations in Sweden was only 48 per cent.Since the economic crisis of the early 1990s, Swedish governments have rolled back the state and introduced market reforms in sectors such as education, health and pensions. Economic freedom has increased in Sweden while it has declined in the UK and USA. Sweden's relative economic performance has improved accordingly.
Keywords: 330; Economic growth; Welfare state; Economic order; Economic reform; Sweden; Wirtschaftswachstum; Sozialstaat; Wirtschaftsordnung; Wirtschaftsreform; Schweden